Safety, diagnostic accuracy and therapeutic efficacy of digital single‐operator cholangioscopy. Issue 6 (1st July 2018) - Lenze, Frank; Bokemeyer, Arne; Gross, Dina; Nowacki, Tobias; Bettenworth, Dominik; Ullerich, Hansjoerg
Abstract : Background: Digital single‐operator cholangioscopes (digital SOCs), equipped with an improved image quality, have been recently introduced. Objective: The aim of this study is to evaluate the safety and diagnostic and therapeutic efficacy of digital SOCs (Spyglass™ DS). Methods: Sixty‐seven digital SOC procedures performed between 2015 and 2017 were retrospectively analyzed. Results: The most frequent indications for examination were indeterminate biliary strictures (61.2%) and biliary stone disease (23.9%). In 25 patients (37.3), visual findings predicted malignancy with a sensitivity of 88.9%, a specificity of 97.6%, a positive predictive value (PPV) of 96.0% and a negative predictive value (NPV) of 92.9%. For histological analysis, forceps biopsies were performed in 29 patients (43.2%). Compared with visual findings, forceps biopsies yield a lower diagnostic efficacy in diagnosing malignancy (sensitivity 62.5%, specificity 90.0%, PPV 90.9%, NPV 60.0%). Therapeutic interventions were performed in 19 patients with a technical success rate of 89.4%. Adverse events were observed in 17 patients (25.4%). Of these, 11 patients (16.4%) suffered from severe adverse events (pancreatitis, cholangitis or major bleeding), which led to a prolonged hospital stay. Conclusion: Digital SOCs have excellent diagnostic and therapeutic efficacies, but are accompanied by high rates of adverse events; therefore, physicians should use digital SOCs in carefully selected cases.